Pengaruh Kontrol Diri Terhadap Perilaku Menyontek pada Siswa - Dian Fitriani; Siti Fitriana; Alis Nihlatin Nisa (Universitas PGRI Palembang, 2024)
This research hopes to conclude the impact of self-control on cheating behavior among students in the software development and GIM focus on program at SMKN 2 Semarang. The general population in this study was 224 with an illustration of 152 students. This research uses a quantitative procedure with a clear immediate backslide analysis strategy with the help of SPSS 24 in taking care of the data. The data combination contraptions used in this research were a transformation of the self-control scale from De Ridder et al (2012) and a variation of the cheating behavior scale from Gardner and Kenneth (1988), in the two scales using a Likert scale. The consequences of this study express that self-control influences cheating behavior, where the higher the self-control an understudy has, the lower the cheating behavior finished by students or the reverse way around, the lower the self-control an understudy has, the higher the cheating behavior did by students. This ought to be noticeable from the aftereffect of the speculation test that the decided F value is 162,332 with a significance level of 0.000 < 0.05, and the connection value (R) is 0.721. From the outcome data, a coefficient of confirmation (R Square) is gotten of 0.520, and that infers that the effect of the free variable (self-control) on the dependent variable (cheating behavior) is 52.0%.